The Chemical Properties and the Combustion Duration of Fuel Briquettes from Corn Kernel Residues, Thailand - et. al., Arunpak Pitakpong, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was studied the feasibility of using corn kernel residues from the plants to manufacture the frozen sweet corn to make the fuel briquettes. The initial stage of the research was the analysis of the chemical properties of corn kernel residues. It found that had the moisture content of 0.00%, volatile matter content of 79.03%, ash content of 2.30%, fixed carbon content of 54.28%, and heating value of 4217.1 calories per gram, had properties that could be used to make the fuel. Then, mixed the corn kernel residues with emulsifiers such as cassava starch at the ratio of 10:0:1, 10:1:1, and 12:1:1 and then compressed the briquettes. The compressed briquettes were obtained to test the chemical properties and the combustion such as heating value, moisture content, volatile matter content, fixed carbon content, ash content, and the combustion duration. The results of this research found that the compression of the corn kernel residues at the ratio of 10:1:1 is the most suitable proportion due to easy compression, high strength, and low ignition time. It had the moisture content of 0.00%, volatile matter content of 75.05%, ash content of 1.41%, fixed carbon content of 54.77% heating value of 3923.2 calories per gram, and the combustion duration of 111.67 minutes.